Journalism ethics: the dilemma, social and contextual constraints - Lai Oso; Raheemat Adeniran; Olasunkanmi Arowolo (Cogent Social Sciences)
Journalism, with its claim to professionalism, is guided in its practice by ethical codes which prescribe what is considered ‘good work’. This theoretical article argues that, though based on certain universal prescriptions, ethics is socially and culturally situated. The observance of the codes is socially determined based on the prevailing moral and political conditions. It is also argued that the issue of the type and quality of representations available in the media should also be of concern when we discuss ethics. The article discusses some of the social constraints to the observance of ethics within the Nigerian context and argues for the need to pay greater attention to addressing the material and economic barriers to media access and representation.